Designing, Fabricating And Characterizing A Microfluidic Capacitor - Raymond Anthony Anthonysamy (Universiti Malaysia Perlis, 2008)
Today, being the dawn of a new technology wave, Micro electromechanical Systems or MEMS have promised a new beginning to a wide spectrum of fields. Microfluidics marked another milestone in this area as highly effective devices with their many advantages over macro devices. Its compact size,smaller volumes of samples and cheaper fabrication cost, low power consumption, multifunctionality and parallelism of analysis have contributed to the increased need for such devices. This sparked the birth of Microfluidic capacitor. This project, integrates three areas; designing, fabricating and electrically characterizing a Microfluidic capacitor. The main insulator channel is replaced with a liquid instead of the usual solid state material. The conductive material will be interdigitated electrodes of aluminium origin. The device is fabricated using standard semiconductor processing techniques. Since the insulator is substituted with fluid, thus the name Microfluidic capacitor. The application of this device would be in portable blood analyzers, DNA and proteomic chips, lab-on-a-chip system, micro total analysis system, DNA sequencing, smart sensors in food packaging and other newer applications.